ANALISIS PENGARUH PEMAHAMAN DAN KESADARAN WAJIB PAJAK DAERAH TERHADAP KEPATUHAN MEMBAYAR PAJAK DI KOTA PONTIANAK - Risal; Sutanto, Burhan (Jurnal Akuntansi, Auditing dan Investasi, 2021)
This research aims to determine the effect of understanding and awareness of local taxpayers on compliance with paying taxes in the city of Pontianak. Sampling in this research using simple random sampling. Data collection techniques using observation, interviews, questionnaires. While hypothesis testing is done by using multiple regression analysis techniques. Based on the results of the analysis, the understanding variable has a significant effect on tax compliance, while the taxpayer awareness variable has no effect on tax compliance.